The effect of stressors on the biochemical composition of new introduced Persica vulgaris (Mill.) varieties in the moisture subtropics of the Krasnodar territory - Y. S. Abilfazova (Новые технологии)
Introduced Persica vulgaris (Mill.) varieties grown in the Institute for Floriculture and Subtropical Crops have been characterized. In order to identify promising varieties of different ecological and geographical origin for cultivation in the conditions of Sochi by biochemical analyzes methods, the Collins, Maykrest, Dixired, Redhaven (st.), Big Top, Veteran and Fayette varieties have been studied. The results of the biochemical analysis of new peach varieties are given: quantitative content of sugar, acidity, dry matter and vitamin C. Sugar-acid ratio has been established, the ratio of which is influenced by the peach ripening period and the climatic conditions of the subtropics of Russia.